Utility of vector flow mapping technology in quantitative assessment of carotid wall shear stress in hypertensive patients: A preliminary study - He, Lan; Cai, Yundan; Feng, Yuhong; Wang, Wenwen; Feng, Tienan; Shen, E.; Yang, Shaoling (Frontiers in Cardiovascular Medicine, 2022)
Background：The blood flowing in the arterial lumen acts on the surface of the vessel wall to form wall shear stress (WSS). To date, there has been limited research on the utility of non-invasive technology in accurately quantification of the carotid WSS in patients with hypertension. Objective: This study aims to explore the usage of vascular vector flow mapping (VFM) in quantitatively assessment carotid WSS in hypertensive patients at an early stage and validate its clinical utility. Methods: A total of 50 individuals confirmed without carotid plaques were grouped into the hypertension group (n=25) and the control group (n=25) according to blood pressure. Using ALOKA LISENDO 880 Color Doppler Ultrasound, L441 3-15 MHZ probe longitudinal section scan to determine the regions of interests (ROIs) of the common carotid artery. VFM - based WSS measurements were obtained by selecting the ROI with optimal image quality from three full cardiac cycles. WSS-derived measurements including WSSmax, WSSmin ,and WSSmean were analyzed and compared between hypertension and control group. In addition, the correlation between WSS-derived measurements and the carotid artery intima-media thickness (IMT) were also analyzed. Results: ① The WSSmax were found to occur in the systolic, while WSSmin were in the diastolic phases of a cardiac cycle.. There were significant statistical differences in WSSmax and WSSmean between patients with hypertension and the control group. Specifically, patients with hypertension had significantly decreased WSSmax and WSSmean than that of the control group (WSSmax:1.781 ± 0.305 Pa vs. 2.286 ± 0.257 Pa; WSSmean:1.276 ± 0.333 Pa vs. 1.599 ± 0.293 Pa, both p<0.001); There was no statistical difference in WSSmin between groups (0.79 ± 0.36 vs. 0.99 ± 0.42, p=0.080). Additionally, WSS-derived parameters were negatively correlated with the IMT using the Spearmen coefficient analysis (p<0.001). Conclusion: The vascular VFM technology enables quantitative assessment of carotid WSS in hypertension patients at an early stage, which maybe provide a new detection method for the early clinical evaluation of vascular function.